Towards an enhanced control of protein crystallization: seeded batch lysozyme crystallization in a meso oscillatory flow reactor - Castro, Filipa (2022)
Protein crystallisation has been shown as a viable alternative to conventional protein purification methods. However, the stochastic and spontaneous nature of the primary nucleation process makes protein crystallization difficult to control. An approach often used in the crystallization of small organic and inorganic molecules to improve the reproducibility of the process and better control the crystallization outcome is seeding. This study presents for the first time the investigation of seeding on batch protein crystallization in a meso oscillatory flow reactor (meso-OFR). Seeded and unseeded lysozyme batch crystallization experiments were carried out, where the influence of the initial lysozyme concentration (initial supersaturation) and the seed quantity on the onset of nucleation, crystal properties and yield was assessed. No major influence of the seed quantity on the product crystal size was verified for the initial lysozyme concentration of 20mgmL-1 (below the secondary nucleation threshold - SNT), while for the initial lysozyme concentration of 25mgmL-1 (above the SNT) the onset of nucleation and mean crystal size significantly decrease with increasing seed quantity. Further, crystal yield increases with both the initial lysozyme concentration and seed quantity. Overall, the results highlight seeding as a promising technique to improve control over the crystallization time and product crystal size.